The role of students' age, problem type and situational context in solving mathematical word problems - Vlahović-Štetić, Vesna (Array, 2005)
The aim of this research is to verify hypotheses regarding the importance of understanding situation in mathematical word problems that follow from Reusser’ s SPS (Situation Problem Solver) model by exploring efficiency of children’ s mathematical word problems solving as a function of age, problem type and situational context of the problem. Children of three age groups participated in the study: preschool kindergarten group, first grade and second grade students. The final sample was formed of 67 kindergarten children, 79 first grade students and 85 second grade students. Testing was conducted by 20 specially trained senior psychology students. Two categories of word problems were used: change problems and compare problems. Every child was tested twice, one time with neutral context problems and other time with familiar context problems. Repeated measures analysis of variance with age, situational context and problem type as independent variables was performed with children’ s performance as a dependent variable. The main effects of age, situational context and problem type were significant, as well as the interaction of age and problem type. Our research results indicate that older children are more successful than younger children in solving mathematical word problems and that the children’ s performance on the change problems is better than on compare problems. Results also showed that children’ s performance on the problems with familiar context was better than performance on the problems with neutral context. These results confirm Reusser’ s essential hypothesis that adding additional sense to the problem text would facilitate designing the situational model of the problem.